Determinants of export supply in Pakistan: A sector wise disaggregated analysis - Sayed Irshad Hussain; Akhtar Hussain; Muhammad Mehboob Alam (Cogent Economics & Finance, 2020)
This study aims to investigate the impact of supply-side factors on the export performance of Pakistan at a disaggregated level. It has identified major export categories of Pakistan and constructed a novel time-series data set of each of these categories from 1971 to 2014. Using autoregressive distributed lag (ARDL) model (bound testing), the sectoral focus confirms that major export categories respond differently to changes in various factors of export supply in the long-run. For instance, the relative prices have a larger impact on the export performance of raw materials and value-added manufactured products. Similarly, the cost of production has higher effects on the growth of value-added manufactured and cotton waste exports. On the contrary, production capacity and domestic demand pressure have significantly influenced the export supply almost all manufactured and primary export categories in the long-run. In the short-run, the relative price, cost of production, and production capacity showed mixed effects for the export supply of many primary and manufactured export categories while domestic demand pressure hypothesis is valid in most cases. The study concludes that the factors determining the export supply are changing across the export categories. Hence, it is suggested that the government must revisit the export policy and make the new policy in line with new sectorial realities in order to expand the export sector of the country.
Keywords: F10; F14; C22; 330; exports; supply function; ARDL approach; disaggregated analysis